Bond portfolios and two-fund seperation in the Lucas asset-pricing model - Kenneth L Judd; Felix Kubler (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
The two-fund separation theorem from static portofolio analysis generalizes to dynamic Lucas-style asset models only whern a consol is present. If all bonds have finite maturity and do not span the consol, then equilibrium will deviate, often significantly, from two-fund separation even with the classical preference assumptions. Furthermore, equilibrium bond trading volume is unrealistically large, particularly for long-term bonds, and would be very costly in the presence of transaction costs. We demonstrate that investors choosing two-fund portofolios with bond ladders that approximately replicate consols do almost as well as traders with equlibrium investment strategies.This result is enhanced by adding bonds to the collection of assets even if they are not necessary for spanning. In light of these results, we argue that transaction cost considerations make portofolios using two-fund separation and bond laddering nearly optimal investment strategies.
Keywords: 330; Dynamically complete markets; general equilibrium; consol; bonds; interest rate fluctation; reinvestment risk; bond laddering; Capital Asset Pricing Model; Anleihe; Theorie